FAO agricultural services bulletin; N126 - FAO (FAO, 1997)
These guidelines have prepared to assist those countries whcich have moved, or are in the process of moving, towwards a liberalised system for marketing agricultural produce and who whish to maintain a strategic grain reserve to guard agaist possible failures of the free market to cope adequately for the food needs of the population.